The influence of technological conditions on the emission of welding fume due to welding of stainless steels - J. Matusiak; A. Wycioelik (Metalurgija, 2010)
Welding of stainless steel is very popular, which consequently is the reason for growing concern for the working environment at welding stations. Chromium is the basic alloying element of all groups of stainless steels. Majority of those steel grades contains nickel. Compositions of the elements occurring in welding fume have a probable or confirmed carcinogenic effect. The article shows the results of research of the relations between selected groups of stainless steels as well as technology parameters of arc welding processes and the welding fume emission, total chromium, chromium (VI) and nickiel contents in the fume.